PENGARUH PIJAT LAKTASI TERHADAP PENGELUARAN KOLOSTRUM PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS BANDUL KABUPATEN KEPULAUAN MERANTI` - Risna Julita; Wira Ekdeni Aifa; Rifa Yanti; Fajar Sari Tanberika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Colostrum is the first milk that comes out, often yellow or can also be clear, which contains living cells that resemble white blood cells that can kill germs so that they can protect the baby's body from various infectious diseases. The theory argues that things that stimulate colostrum release, one of which is by doing lactation massage. Lactation massage is a massage along both sides of the spine. The purpose of this study was to determine the effect of lactation massage on colostrum release in postpartum mothers in the Working Area of the Bandul Health Center, Meranti Islands Regency. The type of research used in this study is quantitative research with a Pre-Experimental research design with a post-only design approach with a control group. The research time was from June to December 2025. The population in this study were 32 postpartum mothers with a sample of 32 respondents divided into 2 groups, namely 16 intervention groups and 16 control groups with a Purposive random sampling technique. The instruments used were SOPs and observation sheets. The results of the univariate study showed that the average colostrum output in postpartum mothers before being given to the intervention group was 2.25 and after the intervention was 15.88, while the average colostrum output in postpartum mothers before the control group was 1.94 and after the control group was 6.88. The results of the analysis using the paired t-test statistical test obtained a p-value = 0.000. The research output is a journal. The conclusion is that there is an effect of lactation massage on colostrum output in postpartum mothers in the working area of the Bandul Health Center, Meranti Islands Regency. Suggestions for mothers who are breastfeeding are to do lactation massage so that breast milk production increases.Keywords: Lactation Massage, colostrum production, and Post Partum mothers